Connective tissue disease : a comprehensive guide. - Roccatello, D. (Dario); Emmi, Lorenzo (Rare diseases of the immune system, 2016)
In this volume devoted to systemic lupus erythematosus (SLE) and Sj©œgren syndrome, leading specialists from different disciplines present the latest research findings on many aspects of the diseases and describe the most recent trends in treatment, such as the <U+00CC><U+0081>́<U+0093>́<U+0093>treat to target<U+00CC><U+0081>́<U+0093>́<U+0093> approach. Both basic science and clinical medicine are addressed, with emphasis on the most promising clinical and laboratory-based studies. The coverage is comprehensive in scope, encompassing, for example, epidemiology, pathogenesis, autoantibodies and biomarkers, disease manifestations, involvement of different organs or systems, relationships with other disorders, biological therapy of SLE, and systemic treatment of Sj©œgren syndrome. Readers will find this first volume of Connective Tissue Disease to be an excellent source of information on the current understanding of, and clinical approach to, SLE and Sj©œgren syndrome that clearly conveys the progress made in recent years.